Spatial Trends of Land Surface Temperature over some selected urban regions in Sri Lanka using remote sensing - Sanjeewani, R.M.S.S.; Manawadu, L. (Asian Journal of Geoinformatics, 2016)
Increase of temperature in urban areas is a vital issue in most part of the world with urbanization. Land surface temperature (LST) varies with the nature of different urban surfaces. Most urban areas of the Sri Lanka possesses a messy urbanization or urban sprawl according to World Bank creating many issues like increase of urban temperature. Studies on land surface temperature over urban areas except Colombo is rarely found in Sri Lanka. This study aims to detect spatial trends of LST over some selected urban areas (Kurunegala, Trincomalee, Anuradhapura and Badulla) in Sri Lanka from 1988 to 2016. LST is derived using Landsat images of 1988, 1997, 2000, 2010 and 2015 and Q GIS and ERDAS is used to calculate LST. Zonal statistics and spatial autocorrelation in ArcGIS is used to identify different vulnerability levels and spatial analysis. Accordingly area of temperature more than 300C has increased considerably by 2010 in Anuradhapura and southern part is highly vulnerable for higher temperature. Spatial pattern of temperature in Kurunegala seems followed by transport network of the area that higher temperature can be witnessed along and beside Colombo, Negambo, Puttalam and Dambulla roads. Higher temperature in Trincomalee urban council is distributed in Trincomalee town area and suburbs. In case of Badulla urban council same as in Kurunegala, initially area with higher temperature can be seen in the middle of city and by 2015 vulnerability has spread along and beside Mahiyanganaya road and A5 road as the city grows up. These results can be considered in urban planning, designing and policy making so as to minimize the vulnerability and bring out strategies for mitigating the vulnerability of higher temperature since these urban areas is still growing.
Keywords: Landsat, ERDAS, Q GIS, Spatial Autocorrelation, Zonal Statistics